Oxidative stress in dogs with coccidiosis - Kizil, O.; Yuce, A. (Ecole Nationale Veterinaire Toulouse, 2009)
The aim of this study was to determine the occurrence of an oxidative stress situation in dogs with coccidiosis. For that, the coccidiosis diagnosis was confirmed in 10 dogs presenting compatible clinical symptoms (bloody diarrhoea, weight loss and dehydration) by detection of oocysts in stool samples whereas 10 apparently clinically healthy dogs without oocyst in stool served as negative controls. Two coccidian species were identified after stool culture: Isospora canis in 7 dogs and I. ohioensis in 3 dogs. Plasma MDA concentrations were determined as a marker for lipid peroxidation and plasma glutathione peroxidase (GSHPx) and catalase (CAT) activities coupled to plasma glutathione (GSH) and serum vitamins C, E, A and beta-carotene concentrations were measured for evaluating the antioxidant efficiency. Marked increases of plasma MDA concentrations compared to healthy dogs were evidenced in infected dogs (P < 0.05) whereas all antioxidant compounds except for GSHPx and beta-carotene were significantly depressed in the infected group. In addition, plasma MDA concentrations as well as the variations of the CAT activities and of the concentrations of the vitamins A and C were significantly associated with the severity of clinical signs. Furthermore, in the infected group, a positive correlation was found between the vitamin A concentrations and the CAT activities (P < 0.01) while vitamin C concentrations were negatively associated with CAT activities and with vitamin A and beta-carotene concentrations (P < 0.05). These results demonstrate the involvement of the oxidative stress as an aggravating factor during coccidiosis in dogs.
Keywords: Dog; oxidative stress; antioxidant status; coccidiosis; Isospora canis; Isospora ohioensis